Investigating the Effect of Environment on the Synthesis of Nickel and Nickel Oxide Nanoparticles Using the Laser Ablation Method with a Nanosecond Fiber Laser - Shahin Torkamani; Hamed Naderi-Samani; Reza Shoja Razavi; Mohammad Gavahian Jahromi; Ehsan Naderi-Samani; Mohammad Reza Borhnai; Atefeh Heidarian (Journal of Advanced Materials in Engineering)
Introduction and Objectives: Nickel nanoparticles are utilized in electronic printing, multilayer ceramic capacitors, magnetic devices, and supercapacitor electrodes in the electronics industry due to their favorable physical, chemical, and magnetic properties, low cost, and optimal sintering temperature. The objective of this study is to synthesize nickel nanoparticles via laser ablation in liquid.Materials and Methods: To characterize the synthesized nanoparticles, field-emission scanning electron microscopy, dynamic light scattering, X-ray diffraction, and ultraviolet-visible spectroscopy were employed.Results: The results revealed that nanoparticles synthesized in distilled water consisted of nickel nanoparticles with FCC crystalline structure and a nickel/nickel oxide (Ni/NiO) core-shell structure. These particles exhibited an average size of 70 nm, spherical morphology, and a rough surface. In contrast, nanoparticles synthesized in a solvent containing Polyvinylpyrrolidone as a stabilizer comprised pure nickel nanoparticles with an average size of 60 nm, spherical morphology, and an FCC crystalline structure. The Polyvinylpyrrolidone-stabilized nanoparticles, owing to their uniform morphology, narrow particle size distribution, and absence of oxide formation, are a promising candidate for nickel nanoparticle synthesis.Conclusion: The nickel nanoparticles synthesized in the Polyvinylpyrrolidone-containing solvent, due to their optimal morphology, uniform particle size distribution, and lack of oxide formation, are well-suited for the production of conductive inks.